Dorsalis pedis psuedoaneurysm: A complication followed extensor tendoscopy of the ankle in a non-tuberculosis patient with tenosynovitis with rice body formation. Issue 2 (June 2016) - Lui, T.H.
Highlights: Tenosynovitis with rice body formation is very rare in the ankle. Extensor tendoscopy of the ankle is a feasible approach for extensor tenosynovitis. Vascular injury with pseudoaneurysm formation is a complication of extensor tendoscopy of the ankle. Abstract: Tenosynovitis with rice body formation is very rare in the ankle region. A case of this condition in a non-tuberculosis patient was presented. He was treated by extensor tendoscopy of the ankle. The tenosynovitis subsided after the procedure. However, it was complicated by formation of a dorsalis pedis pseudoaneurysm.